A rare case of hydatid cyst in the breast in a tertiary care hospital in Bangalore, Karnataka, India - Dr. Venkatesh Vikram. H. C.; Dr. Manasa S. (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2020)
Hydatid disease is a well-known entity since the era of Hippocrates. Although breast is one of the rare sites for the occurrence of hydatid disease, it has been well evaluated with the various newer imaging modalities and its imaging features are well described in the literature. A 41-year-old female presented with a painless well-defined lump in the right breast without any history of pain, trauma, discharge from the nipple, fever, or drug misuse. This case was diagnosed preoperatively by FNAC, ultrasound, and was confirmed by surgery. Hydatid disease of the breast should form the part of the differential diagnosis of cystic diseases of the breast especially in an endemic country like India. Awareness of this entity can make the pre-operative diagnosis even without cytological examination, which is very helpful in the management of the patient.